But... What do we Really mean by Formative and Shared Assessment?: Usual Confusions and Practical Reflections - David Hortigüela; Ángel Pérez-Pueyo; Gustavo González-Calvo (Universidad Autónoma de Madrid, 2019)
It is fundamental to reflect on the aims and possibilities of the use of formative and shared evaluation (FSA) in educational contexts. Although the literature about its effects on diversity of variables is abundant and tedious, it is not so much at the time of clarifying certain pedagogical errors in its implementation. This is necessary, even more so now, where its dissemination has been very high in recent years. The objectives of this study are two: a) to present the most common confusions when using FSA and b) to establish reflections and practical considerations for its proper use. The topics analyzed are: 1) formative assessment/continuous qualification; 2) the teacher as the only feedback agent; 3) no delimitation of the criteria in advance; 4) not allow previous deliveries; 5) not guarantee the jump to the qualification in a pedagogical way; 6) not to associate evaluation procedures with their respective instruments; 7) use the evaluation for purely academic purposes. It is intended that this manuscript may be of special interest and usefulness for all teachers interested in the field of evaluation, and as a consequence to improve their educational practice. It must be remembered that education is much more than assessment, but without it, its effects are more limiting.